ENGINEERING MANAGEMENT OF INFLUENCE OF PERFORMANCE INDICATORS OF RELIABILITY AND MAINTAINABILITY OF GRAIN HARVESTER ON EFFICIENCY OF ITS MACHINE USER - Titova, L. L.; Nadtochiy, O. V. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2022)
The article formulates methodological approaches of engineering management to maintain the efficiency of combine harvesters, for which during the entire period of operation it is associated with the complexity of their structure through the use of automated and hydraulic devices, electronics, increased productivity emphasizes the importance of combine failure for technical reasons. In the current development of mechanization of agricultural production, in the author’s opinion, should be based on two equally important points, namely the growth of production of the agro-industrial complex and the rational reduction of its cost. Completion of the combine fleet of farms with domestic or foreign machines should be carried out taking into account these factors, as well as other requirements of today. The authors have developed a method for evaluating the efficiency of combine harvesters on two criteria of reliability, namely indicators of reliability and maintainability, on the specific total cost per hectare of the area harvested of grain crops. The process of machine use of the combine is considered in the form of a queuing system, where the device is considered to be the harvesting machine, from which comes the flow of failures that cause the equipment to stand still. The article obtains comparative dependences of specific total costs on these reliability indicators, which are characterized by failure time, recovery time and other indicators that affect their efficiency: the book value of the combine, service life, cost of sales, crop yields and harvest duration on the example of grain combine Class Mega-370. The dependence is obtained, which shows that the harvest will last 14 days with the help of 24 combine harvesters with downtime not exceeding 1.24 hours, or 25 combine harvesters with downtime of 1.9 hours. The obtained results, as a prospect of further research, can be used by agricultural farms in completing the combine fleet of both domestic and imported models of combine harvesters.